FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN SEKTOR INDUSTRI - Ricardo, Willy; Iskak, Jamaludin (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to examine the effect of leverage, firm size, dan working capital turnover on profitability of industry sector companies listed on the Indonesia Stock Exchange during 2019-2021. Sample was selected using purposive sampling method and the valid data was 19 companies. Data processing techniques using multiple regression analysis with the Eviews 10 program and Microsoft Excel 2013. The results of this study indicate that leverage and working capital turnover have insignificant effect on profitability, and firm size has a positive and significant effect on profitability. The implication is the need to increase profitability to make company be able to operate their business which is influenced by firm size dan working capital turnover to expand its business.